Recognition of the Phanerozoic “Young Granite Gneiss” in the central Yeongnam Massif - Song, Y.; Lee, H.; Park, K.; Fitzsimons, Ian; Cawood, Peter (Springer, 2015)
Up to now, all the high-grade gneisses of the Korean peninsula have been regarded as Precambrian basement rocks and presence of the Phanerozoic high-grade metamorphic rocks have remained unknown. However, such granite gneiss is discovered through this study from the central Yeongnam massif near Gimcheon. SHRIMP zircon U-Pb age determinations on the granite gneiss, having well-developed gneissic foliations and migmatitic textures, reveal concordant age of ca. 250 Ma indicating the Early Triassic emplacement of this pluton, which is in contradict to the previous belief that it is a Precambrian product. Even though the granite gneiss reveals well-developed gneissic foliations and some zircons show rather low Th/U ratios, the metamorphic age has not been determined successfully. However, the age of metamorphism can be constrained as middle Triassic considering the absence of any evidences of metamorphism from the nearby granitic plutons having emplacement ages of ca. 225 Ma. Early Triassic emplacement and subsequent Middle Triassic metamorphism of the granite gneiss from the Yeongnam massif bear a remarkable resemblance to the case of South China block. We suggest the possibility that Early to Middle Triassic metamorphism of the Korean peninsula might be products of the intracontinental collisional events not directly related with the Early Triassic continental collision event.